(untitled) (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2025)
Social media platforms have become places where various individuals express their views on current issues. The Childfree phenomenon has become a widely discussed topic on social media, especially in Indonesia, along with the increasing number of individuals choosing not to have children after marriage. On one hand, the decision to adopt a Childfree lifestyle reflects individual freedom in determining the direction of one’s life, which is part of human rights. However, on the other hand, the decision to adopt a Childfree lifestyle has garnered both support and opposition within society, especially in the context of cultural, religious, and demographic values. This phenomenon is rapidly developing with the support of globalization and easy access to information, which allows for an increasingly open discourse on individual freedom in making life choices. This research aims to analyze the childfree phenomenon on social media from the perspective of a demographic threat, human rights perspective, and maqashid sharia. This research uses qualitative methods, with interview techniques involving informants from various backgrounds, including religious figures, medical personnel, and academics in the city of Palangka Raya. The research results indicate that there are significant differences in perspectives on this phenomenon.From a religious perspective, being childfree is viewed as contrary to the principles of maqashid sharia, especially in the aspect of hifz nasl (preservation of lineage). Meanwhile, from a medical perspective, the decision not to have children is associated with certain health risks for women.